The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/genes12091399
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Profiling of 2OGD Superfamily Genes from Three Brassica Plants

Abstract: The 2-oxoglutarate and Fe(II)-dependent dioxygenase (2OGD) superfamily is the second largest enzyme family in the plant genome, and its members are involved in various oxygenation and hydroxylation reactions. Due to their important biochemical significance in metabolism, a systematic analysis of the plant 2OGD genes family is necessary. Here, we identified 160, 179, and 337 putative 2OGDs from Brassica rapa, Brassica oleracea, and Brassica napus. According to their gene structure, domain, phylogenetic features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Before the separation of Brassica and Arabidopsis lineages, the WGD event was experienced, and then another whole-genome triploid (WGT) event was experienced [ 65 , 66 ]. After the WGT event, the gene family menbers changed, and the amplification phenomenon was also identified in the 2OGD gene family [ 67 ]. WGD is closely related to the evolution of plants and the origin of polyploidy and two hypotheses had been proposed to explain the origin and evolution of polyploidy [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Before the separation of Brassica and Arabidopsis lineages, the WGD event was experienced, and then another whole-genome triploid (WGT) event was experienced [ 65 , 66 ]. After the WGT event, the gene family menbers changed, and the amplification phenomenon was also identified in the 2OGD gene family [ 67 ]. WGD is closely related to the evolution of plants and the origin of polyploidy and two hypotheses had been proposed to explain the origin and evolution of polyploidy [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kawai et al first identified the 2OGD superfamily in Arabidopsis , rice, Picea abies , Selaginella moellendorffi , Physcomitrella patens and Chlamydomonas reinhardtii , which own 130, 114, 142, 74, 66 and 41 members respectively [ 3 ]. Followed by the 2OGDs identification in corn [ 38 ], tomato [ 6 ], Salvia miltiorrhiza [ 39 ], Brassica rapa , Brassica oleracea and Brassica napus [ 40 ], which have 103, 159, 132, 160, 179 and 337 members respectively. In this study, 163 Vv2OGD members were identified in grape, which is the third-biggest 2OGD family in identified species, only after Brassica oleracea and Brassica napus .…”
Section: Discussionmentioning
confidence: 99%
“…The deduced protein sequences of the four BocODDs contained Fe( 2+ ) and the 2-oxoglutarate (2OG)-dependent dioxygenase domain, which catalyze the oxidation of an organic substrate using a dioxygen molecule, mostly by using ferrous iron as the active site cofactor and 2OG as a co-substrate [ 27 ]. The 2OG gene family can be classified into three classes—DOXA, DOXB, and DOXC—based on their amino acid sequences [ 28 ]. The DOXC class is involved in the biosynthesis of various phytochemicals [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 2OG gene family can be classified into three classes—DOXA, DOXB, and DOXC—based on their amino acid sequences [ 28 ]. The DOXC class is involved in the biosynthesis of various phytochemicals [ 28 ]. ODDs have been classified into DOXC and catalyze the biosynthesis of goitrogenic 2-hydroxy-3-butenyl glucosinolate in Arabidopsis [ 16 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation